2019
DOI: 10.1021/acsomega.8b03173
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Toxicity Prediction via Simple Features Using Shallow Neural Networks and Decision Trees

Abstract: Toxicity prediction of chemical compounds is a grand challenge. Lately, it achieved significant progress in accuracy but using a huge set of features, implementing a complex blackbox technique such as a deep neural network, and exploiting enormous computational resources. In this paper, we strongly argue for the models and methods that are simple in machine learning characteristics, efficient in computing resource usage, and powerful to achieve very high accuracy levels. To demonstrate this, we develop a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 71 publications
0
55
0
Order By: Relevance
“…[74]. Abdul et al [75] developed a task-based chemical toxicity prediction framework, and used a decision tree to obtain an optimum number of features from a collection of thousands of them, which effectively help chemists perform prescreening of toxic compounds effectively.…”
Section: Classical Qsar Methodsmentioning
confidence: 99%
“…[74]. Abdul et al [75] developed a task-based chemical toxicity prediction framework, and used a decision tree to obtain an optimum number of features from a collection of thousands of them, which effectively help chemists perform prescreening of toxic compounds effectively.…”
Section: Classical Qsar Methodsmentioning
confidence: 99%
“…[71] who showed that positive transfer learning is conditioned by sharing a significant amount of input data whose labels are correlated. In general, other studies [72,73,74,75] reported that FNN performs the best for a variety of chemoinformatics problem, but only for some metrics and datasets.…”
Section: Deep Learning For Chemoinformaticsmentioning
confidence: 91%
“…SwissADME webserver was used for computing ADMET properties of top-scoring compounds such as Lipinski rule of 5 [50], gastro-intestinal (GI) absorption, blood-brain barrier (BBB) permeant, cytochrome inhibition [51,52]. The SMILES format of these compounds was submitted to SwissADME webserver.…”
Section: Lipinski's Rule and Admet Predictionmentioning
confidence: 99%